Evaluation of factors affecting students' performance in tertiary education - Kawtar Tani; Elizabeth Dalzell; Nathan Ehambaranathan; Sheela Murugasu; Anne Steele (Journal of Pedagogical Research, 2019)
The aim of this study is to evaluate factors contributing to poor academic performance of students in higher education.  Data was collected in 2017 from 216 students enrolled in different programmes at a higher education provider in New Zealand. The effect of factors relating to family obligations, work and social commitments, and financial concerns were analysed. Results showed significant relationship between academic performance of students and their attendance. Other significant findings included the relationship between attendance and the level of study; work shift; ethnicity; whether participants had any dependents; and how studies were funded. Implications and limitations of this study are presented.